Evolution of Surface Tension and Hansen Parameters of a Homologous Series of Imidazolium-Based Ionic Liquids - Mayer, Sophie; Bergen, Alexander; Zhai, Ziwen; Trzeciak, Simon; Chu, Junyu; Zahn, Dirk; Koller, Thomas Manfred; Meyer, Karsten; Vogel, Nicolas (Langmuir, 2024)
In this study, we systematically analyze the surface tension and Hansen solubility parameters (HSPs) of imidazolium-based ionic liquids (ILs) with different anions ([NTf2]−, [PF6]−, [I]−, and [Br]−). These anions are combined with the classical 1-alkyl-3-methyl-substituted imidazolium cations ([CnC1Im]+) and a group of oligoether-functionalized imidazolium cations ([(mPEGn)2Im]+) based on methylated polyethylene glycol (mPEGn). In detail, the influences of the length of the alkyl- and the mPEGn-chain, the anion size, and the water content are investigated experimentally. For [CnC1Im]+-based ILs, the surface tension decreases with increasing alkyl chain length in all cases, but the magnitude of this decrease depends on the size of the anion ([NTf2]− < [PF6]− < [Br]− ≤ [I]−). Molecular dynamics (MD) simulations on [CnC1Im]+-based ILs indicate that these differences are caused by the interplay of charged and uncharged domains, in particular in the different anions, which affects the ability of the alkyl chains of the cation to orient toward the liquid-gas interface. An increase in the mPEGn-chain length of the [(mPEGn)2Im][A] ILs does not significantly influence the surface tension. These changes upon variation of the cation/anion combination do not correlate with the evolution of the HSPs for the two sets of ILs. Finally, our data suggest that significant water contents up to water mole fractions of x(H2O) = 0.25 do not significantly affect the surface tension of the studied binary IL-water mixtures.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Alkyls; Anions; Interfaces; Solvents; Surface tension